Modified Microstrip Feed Hybrid Rectangular Dielectric Resonator Antenna for Wireless Tri-Band Applications - Chaitanya B; Manjunathachari K (Measurement Science Review, 2023)
This article reports the Modified Microstrip Feed Hybrid Rectangular Dielectric Resonator Antenna (RDRA). The proposed structure has a ground plane with a plus-shaped slot on an FR4 substrate with a height of 1.6 mm and dimensions of 38 mm x 35 mm. The proposed Dielectric resonator antenna is made of a material with 10 as its dielectric constant, and the dimensions of the DR are 19 x 20 x 18 mm3. The DR is connected to a modified microstrip feed with an octagonal ring through the plus-shaped slot in the ground. The proposed structure operates in frequencies from 2.60 GHz - 2.74 GHz, 3.12 GHz - 3.37 GHz, and 4.25 GHz - 4.37 GHz. The resonant frequency of the final proposed RDRA is 2.68 GHz, 3.26 GHz, and 4.31 GHz, which covers WLAN, WIMAX and Wireless Avionics Intra-Communications (WAIC) applications, respectively. The entire structure was simulated using the CST microwave studio. The simulated results agree with the measured results and both are presented. The compact size, stable radiation pattern and reasonable gain make this antenna suitable for the proposed applications.